2005
DOI: 10.1007/s10750-005-4235-x
|View full text |Cite
|
Sign up to set email alerts
|

Diapause in Monogonont Rotifers

Abstract: This review focuses on more recent findings on the diapause in Monogonont rotifers, since the major reviews by Pourriot

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 98 publications
2
81
0
6
Order By: Relevance
“…Much general information is available on the biology of resting eggs: (1) reviews on structure, diapause duration, and hatching (Gilbert, , , , ; Gilbert & Schröder, ; Pourriot & Snell, ; Schröder, ); (2) studies on the density, viability, and genetic diversity of B. plicatilis eggs in sediment (García‐Roger, Carmona, & Serra, , ; Gómez & Carvalho, ); and (3) a review on cellular and physiological processes occurring during diapause entry and exit (Garcia‐Roger, Lubzens, Fontaneto & Serra, ).…”
Section: Emergence From Resting Eggsmentioning
confidence: 99%
“…Much general information is available on the biology of resting eggs: (1) reviews on structure, diapause duration, and hatching (Gilbert, , , , ; Gilbert & Schröder, ; Pourriot & Snell, ; Schröder, ); (2) studies on the density, viability, and genetic diversity of B. plicatilis eggs in sediment (García‐Roger, Carmona, & Serra, , ; Gómez & Carvalho, ); and (3) a review on cellular and physiological processes occurring during diapause entry and exit (Garcia‐Roger, Lubzens, Fontaneto & Serra, ).…”
Section: Emergence From Resting Eggsmentioning
confidence: 99%
“…Bdelloidea may enter dormancy in any stage of their life cycle (Ricci & Fontaneto 2009), whereas Monogononta produce resting eggs that can remain dry and/or frozen for extended periods before hatching (Gilbert 1974, Schröder 2005 there is little or no evidence of metabolic activity (Clegg 1986(Clegg , 2001. Bdelloidea may enter dormancy in any stage of their life cycle (Ricci & Fontaneto 2009), whereas Monogononta produce resting eggs that can remain dry and/or frozen for extended periods before hatching (Gilbert 1974, Schröder 2005 there is little or no evidence of metabolic activity (Clegg 1986(Clegg , 2001.…”
Section: Physiologymentioning
confidence: 99%
“…Whereas Bdelloidea recover from their dormant stage as soon as water becomes available (Ricci 1998a), hatching of resting eggs of Monogononta is triggered by a more complex mechanism, with temperature and/or light conditions, interacting with the length of desiccation (Minkoff et al 1983, Schröder 2005.…”
Section: Physiologymentioning
confidence: 99%
“…Overall, this conceptual model has been verified in a recent study with B. calyciflorus , which showed that selective sweeps of OP clones invading into CP populations in chemostats could be quantitatively predicted based on such costs of sex and diapause (Stelzer 2011). In natural systems, however, there may be strong adaptive benefits of producing diapausing eggs, most notably bet‐hedging strategies in unpredictable environments (Schroder 2005; Stelzer 2005). Brachionus populations often inhabit small ponds, which may dry up in summer or completely freeze in winter.…”
Section: Introductionmentioning
confidence: 99%